2010
DOI: 10.3350/kjhep.2010.16.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the nonalcoholic fatty liver diseases activity score (NAS) in Korean NAFLD patients and its correlation with clinical factors

Abstract: The simple and reproducible NAS was found to be a useful pathologic grading system in Korean NAFLD patients. However, the proportion of borderline cases based on the NAS was high. The "wait and see" strategy is necessary for evaluating the long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These findings suggest that higher degrees of steatosis result in an increase in inflammatory response and, subsequently, in elevated ALT levels, which might be a predictor of progression of steatosis to steatohepatitis and fibrosis [39]. Lee et al [41] demonstrated that ALT levels were significantly higher in obese cases than controls (with a nonsignificant difference for AST), with 12 cases of 83 having elevated ALT levels. On the other hand, Patton et al [2] concluded that AST was a significant predictor of the NAFLD pattern, fibrosis severity, and NASH in obese children.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that higher degrees of steatosis result in an increase in inflammatory response and, subsequently, in elevated ALT levels, which might be a predictor of progression of steatosis to steatohepatitis and fibrosis [39]. Lee et al [41] demonstrated that ALT levels were significantly higher in obese cases than controls (with a nonsignificant difference for AST), with 12 cases of 83 having elevated ALT levels. On the other hand, Patton et al [2] concluded that AST was a significant predictor of the NAFLD pattern, fibrosis severity, and NASH in obese children.…”
Section: Discussionmentioning
confidence: 99%
“…Again, although the simple and reproducible NAS was found to be a useful pathologic grading system in Korean NAFLD patients, however, the proportion of borderline cases based on the NAS was high. The "wait and see" strategy is necessary for evaluating the long-term prognosis (17). Clinically important differences exist between community general pathologist and expert hepatopathologist in assessing NAFLD using the NAS scoring system.…”
mentioning
confidence: 99%